OPTIMALISASI PERAN HUKUM DALAM TATA KELOLA DAN PENGAWASAN BUMN: KAJIAN PUSTAKA TENTANG UPAYA MEWUJUDKAN BUMN YANG PROFESIONAL, EFISIEN, DAN BERORIENTASI PADA KEPENTINGAN PUBLIK - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article examines the optimisation of the role of law in the governance and supervision of State-Owned Enterprises (SOEs) as an effort to realise SOEs that are professional, efficient, and oriented towards the public interest. Through a literature review approach, the study analyses the legal framework governing SOEs, the implementation of Good Corporate Governance (GCG) principles, and the strengthening of legal oversight mechanisms by both internal and external bodies, including Commissioners/Supervisory Boards, the State Audit Agency, specialised supervisory bodies, the House of Representatives, and law enforcement agencies. The findings indicate that strengthening legal norms, harmonising regulations, enhancing the capacity of officials, and strengthening coordination among supervisory bodies are key to improving SOE governance and ensuring accountability in the management of state finances. Thus, optimising the role of the law serves not only as an instrument for preventing corruption and abuse of authority, but also as a foundation for SOEs to operate professionally, competitively, and in the public interest.